Pengaruh Adversity Intelligence, Motivasi Belajar Terhadap Kesiapan Belajar - Arika Palapa; Moh Zaenal Arifin; Hartoyo Hartoyo (Dinamika Bahari, 2020)
The specific purpose of this study was to examine the effect of Adversity Intelligence of cadets participating in the seafaring expertise test and learning motivation of cadets participating in the seafaring expertise test on study readiness both partially and collectively. This study used a sample of 62 cadets participating in the pre-prala seafarer expertise test in the nautical department. The sampling technique in this study was nonprobability sampling with a purposive sampling method. Based on the research results, it can be concluded as follows: (1) adversity intelligence has an effect on learning readiness, (2) learning motivation has a positive and significant effect on learning readiness, (3) Adversity Intelligence affects learning motivation, ( 4) Adversity Intelligence and learning motivation together have an effect on learning readiness.